The influence of a statewide "Stay-at-Home" order on trauma volume and patterns at a level 1 trauma center in the united states. Issue 11 (November 2020) - Leichtle, Stefan W.; Rodas, Edgar B.; Procter, Levi; Bennett, Jonathan; Schrader, Robin; Aboutanos, Michel B.
Highlights: COVID-related restrictions on public life in the commonwealth of virginia resulted in a temporary 43% reduction in trauma volume. There were no drastic changes in trauma patterns and injury mechanisms in the short term. Trauma patients admitted during the COVID pandemic had higher injury severity and were discharged after shorter hospital length of stays. Some changes in trauma patterns may not manifest until after easing of COVID-related restrictions. Abstract: The COVID pandemic of 2020 resulted in unprecedented restrictions of public life in most countries around the world, and many hospital systems experienced dramatic decreases in non-COVID related patient admissions. We aimed to compare trauma volumes, patient characteristics, and trauma mechanisms at a large, urban Level 1 trauma center in the United States during a state-wide "State of Emergency" and "stay-at-home" order to corresponding historic dates. All adult trauma activations from March 1 through April 30, 2020 and a historic control from March 1 through April 30, 2018 and 2019 were reviewed in the institution's trauma registry. Trauma volumes, patient characteristics, and trauma mechanisms were compared over time as increasingly stricter COVID-related restrictions were enacted in the Commonwealth of Virginia. After declaration of a state-wide "Public Health Emergency" on March 17, 2020, the daily number of trauma activations significantly declined to a mean of 4.7 (standard deviation, SD = 2.6), a decrease by 43% from a mean of 8.2 (SD = 0.3) for the same dates in 2018 and 2019. Trauma activations during COVID restrictions vs. historic control were characterized by significantly higher prevalence of chronic alcohol use (15.5% vs. 6.8%, p < 0.01), higher median (25th – 75th percentile) Injury Severity Score of 9 (5 – 16) vs. 6 (4 – 14), p  = 0.01, and shorter median (25th – 75th percentile) length of hospital stay of 2 (1 – 6) days vs. 3 (1 – 7) days, p  = 0.03. The COVID-related Public Health Emergency and "stay-at-home" order in the Commonwealth of Virginia dramatically reduced overall trauma volumes with minor but interesting changes in trauma patterns.